Accretion Flow Morphology in Numerical Simulations of Black Holes from the ngEHT Model Library: The Impact of Radiation Physics - Koushik Chatterjee; Andrew Chael; Paul Tiede; Yosuke Mizuno; Razieh Emami; Christian Fromm; Angelo Ricarte; Lindy Blackburn; Freek Roelofs; Michael D. Johnson; Sheperd S. Doeleman; Philipp Arras; et al. (Galaxies, 2023)
In the past few years, the Event Horizon Telescope (EHT) has provided the first-ever event horizon-scale images of the supermassive black holes (BHs) M87<semantics>*</semantics> and Sagittarius A<semantics>*</semantics> (Sgr A<semantics>*</semantics>). The next-generation EHT project is an extension of the EHT array that promises larger angular resolution and higher sensitivity to the dim, extended flux around the central ring-like structure, possibly connecting the accretion flow and the jet. The ngEHT Analysis Challenges aim to understand the science extractability from synthetic images and movies to inform the ngEHT array design and analysis algorithm development. In this work, we compare the accretion flow structure and dynamics in numerical fluid simulations that specifically target M87<semantics>*</semantics> and Sgr A<semantics>*</semantics>, and were used to construct the source models in the challenge set. We consider (1) a steady-state axisymmetric radiatively inefficient accretion flow model with a time-dependent shearing hotspot, (2) two time-dependent single fluid general relativistic magnetohydrodynamic (GRMHD) simulations from the H-AMR code, (3) a two-temperature GRMHD simulation from the BHAC code, and (4) a two-temperature radiative GRMHD simulation from the KORAL code. We find that the different models exhibit remarkably similar temporal and spatial properties, except for the electron temperature, since radiative losses substantially cool down electrons near the BH and the jet sheath, signaling the importance of radiative cooling even for slowly accreting BHs such as M87<semantics>*</semantics>. We restrict ourselves to standard torus accretion flows, and leave larger explorations of alternate accretion models to future work.